Rice residue management interventions and irrigation regimes: Impact on soil physical characteristics and moisture storage under wheat in Northern India - KUMAR, MUKESH; SINGH, JAGDISH; CHHINA, R.S.; KAHLON, M.S.; SHARMA, SEEMA (Journal of Soil and Water Conservation, 2025)
The five residue-tillage management interventions of conventional tillage (RRC), zero till without residue (RRZ), happy seeder with residue retention (HS), residue incorporation with super seeder (SS), and residue incorporation with soil inversion through mould board plough (MMC) were tested along with three irrigation regimes of 0.9, 0.6, and 0.3 IW/CPE ratio to understand changes in soil properties and moisture storage under wheat in silt loam soil of North-west India. The HS and RRZ had the highest soil bulk density at 0-15 cm and 15–30 cm soil depths, followed by RRC, SS, and MMC. The HS had the highest mean weight diameter (0.41) and water stable aggregates (45.02) and MMC had the lowest. The surface layer soil organic carbon was significantly higher under SS (5.34 g kg-1) and HS (5.15 g kg-1) than under RRC (4.61 g kg-1). The base infiltration rate (cm hr-1) was highest under MMC (1.24) followed by SS (1.09), HS (0.74), RRC (0.6) and least under RRZ (0.58). It was concluded that wheat crop establishment by happy seeder with residue retention and residue incorporation with super seeder improves soil quality over conventional tillage practise and these may be adopted for sustainable soil health management in North Western IGP and similar agro-ecologies.